Mechanism Research and Experiment of Two-dimensional Gearbox with Output Shaft Rotating and Reciprocating Motion - Wu Shangsheng; Deng Haiyan; Deng Hongjian; Liu Yaping (Jixie chuandong)
A new type two-dimensional gearbox with the output of rotating and reciprocating motion and transmission principle are proposed. The physical model of the two-dimensional gearbox is constructed by using the three-dimensional modeling software Inventor. The reciprocating motion related assembly is designed by applying the method of double eccentricity amplitude adjustment and eccentric wheel structure characteristics,the working principle of the output shaft rotation and axial reciprocating motion mechanism is mainly studied. The kinematics analysis of the model is carried out in software ADAMS and the output characteristics of the axially reciprocating assembly motion are obtained. Based on the theory above,the prototype of the two-dimensional gearbox is developed and manufactured. The plastic extrusion experiment is carried out by mounting the prototype on a single screw extruder. The rationality and feasibility of the two-dimensional gearbox with the output shaft rotation and reciprocating motion are verified.